Kewirausahaan: Membangun Ekonomi Lokal Dan Mengarahkan Masa Depan Berdaya Saing Ditengah Kasus Korupsi Timah 271T Bangka Belitung - Suci Wulandari; Tiara Augus Fitriani; Indah Noviyanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The Bangka Belitung Islands are known to be rich in tin resources so it cannot be denied that most of the people make their living from tin but are now shackled by the 271T corruption case. This study aims to evaluate how big the impact of entrepreneurship is on Bangka Island, especially Central Bangka Regency, after the rise in tin corruption cases which disrupted people's work, apart from that local fishermen were also affected by the existence of sea mines. Entrepreneurship plays an important role in building local economies and guiding a competitive future. This research aims to analyze how the Timah 271T Bangka Belitung corporation can increase its competitive capabilities through entrepreneurship that is oriented towards developing local resources and increasing community participation in the economic development process. This research applies a quantitative approach in its methodology and utilizes a questionnaire as a data collection tool. The population studied was MSME entrepreneurs in Central Bangka Regency, with a total of 39 respondents. The multiple regression analysis used, namely SPSS version 27 software, was used as a data analysis method. The test results show that the coefficient of determination is 0.288, which means that around 28.8% of the variation in the dependent variable can be seen in the independent variables studied. This value shows that the Local Economy and Competitiveness variables influence Entrepreneurship in MSMEs in Central Bangka by 28.8%. The t test results show that Local Economy (X1) has no influence on Entrepreneurship, while Competitiveness (X2) has a significant influence on MSME entrepreneurship in Central Bangka. The results of this research will contribute to the development of effective entrepreneurial strategies to increase the competitiveness of MSME entrepreneurs in Central Bangka and encourage local economic growth.